HUBUNGAN KUALITAS PELAYANAN APOTEK DENGAN TINGKAT KEPUASAN KONSUMEN DI APOTEK BLUNYAH FARMA YOGYAKARTA - Adel Meisita Putri; Endang Setyowati; Galih Kurniawan (Yayasan Nusantara Hasana Berdikari, 2025)
Pharmaceutical services play an important role in the healthcare system, not only in drug dispensing but also in providing information and education. Suboptimal pharmacy service quality may affect customer satisfaction. This study aimed to determine the relationship between pharmacy service quality and customer satisfaction at Blunyah Farma Pharmacy Yogyakarta. This study used a quantitative approach with a cross-sectional design. A total of 300 respondents were selected using purposive sampling. Data were collected through closed-ended questionnaires consisting of 20 items for each variable: service quality and customer satisfaction. Data were analyzed using univariate and bivariate methods with the Pearson correlation test. The quality of pharmacy services was in the good to very good category, with the highest score in the prescription review aspect 90.84% and the lowest in drug information service/PIO 60.04%. Customer satisfaction was in the very satisfied category, with the highest score in the empathy dimension (91.97%) and the lowest in the responsiveness dimension 81.73%. The Pearson test results indicated a positive and significant relationship between service quality and customer satisfaction r = 0.342; p = 0.000 with a moderate correlation strength. There is a positive and significant relationship between pharmacy service quality and customer satisfaction at Blunyah Farma Pharmacy Yogyakarta. The better the service quality, the higher the customer satisfaction tends to be.